1985
DOI: 10.2340/0001555565206213
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors in atopic dermatitis

I. Rystedt

Abstract: A long-term follow-up study (24 years minimum) was made of 955 individuals aged 24-44 years, who had atopic dermatitis (AD) in childhood. The material was divided into two groups; patients who in 1952-56 had been hospitalized on at least one occasion at the Department of Dermatology, Karolinska Hospital, Stockholm (Group 1), and patients who in 1955-56 had been out-patients in the same department (Group 2). At the time of investigation 62% and 40% of the patients in Groups 1 and 2 respectively had ongoing derm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 63 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…They suggest that their report provides evidence for a pathogenesis of delayed type at the basis of AD. Regarding pediatric asthma, it is increasingly appreciated that AD can be associated with respiratory allergy (25-51% of cases) [21]: children with AD can have a latent predisposition to asthma [22], significantly more elevated if they have a smoking mother [23] or an early onset of AD [24]; in addition AD worsens in spring in children allergic to pollens. Studies have also reported that asthma develops in infants aged 0 to 1 year (3).…”
Section: Advances In Biotechnology and Microbiologymentioning
confidence: 99%
See 1 more Smart Citation
“…They suggest that their report provides evidence for a pathogenesis of delayed type at the basis of AD. Regarding pediatric asthma, it is increasingly appreciated that AD can be associated with respiratory allergy (25-51% of cases) [21]: children with AD can have a latent predisposition to asthma [22], significantly more elevated if they have a smoking mother [23] or an early onset of AD [24]; in addition AD worsens in spring in children allergic to pollens. Studies have also reported that asthma develops in infants aged 0 to 1 year (3).…”
Section: Advances In Biotechnology and Microbiologymentioning
confidence: 99%
“…Studies have also reported that asthma develops in infants aged 0 to 1 year (3). Thirty-five percent of 500 children aged 6 years were asthmatic, 50 % if suffering from severe AD, and only 15% if from mild AD [25], showing that asthma starts earlier and more frequently in children affected with more severe manifestations [24,26].…”
Section: Advances In Biotechnology and Microbiologymentioning
confidence: 99%